2013
DOI: 10.1080/17437199.2013.840952
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and HIV-related sexual behaviours among international migrants: a systematic review and meta-analysis

Abstract: This review examines the global literature regarding the relationship between acculturation and HIV-related sexual behaviors among international migrants. Seventy-nine articles published in English-language journals prior to July 2012 met the criteria for inclusion. We conducted a systematic review and subset meta-analysis of correlations between acculturation and five types of sexual behaviors including condom use, multiple partnerships, early sexual initiation, sexually transmitted diseases (STDs), and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 138 publications
2
38
0
1
Order By: Relevance
“…Engaging in risk and unprotected sex has been documented as a coping strategy to deal with stress in migrant (Du & Li, 2015)and non-migrant populations (Brody, Chen, & Kogan, 2010; Deuba et al, 2013; Folkman, Chesney, Pollack, & Phillips, 1992; Muñoz-Laboy, Severson, & Bannan, 2014). The research findings described in the previous sections suggest a potential mechanism by which poor mental health mediates the association between migration stress and sexual risk behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Engaging in risk and unprotected sex has been documented as a coping strategy to deal with stress in migrant (Du & Li, 2015)and non-migrant populations (Brody, Chen, & Kogan, 2010; Deuba et al, 2013; Folkman, Chesney, Pollack, & Phillips, 1992; Muñoz-Laboy, Severson, & Bannan, 2014). The research findings described in the previous sections suggest a potential mechanism by which poor mental health mediates the association between migration stress and sexual risk behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, gender was reported to moderate the relationships between acculturation, and multiple partnerships and unsafe sex [14]. A younger age and the time spent in the host country were found to influence sex while under the influence of drugs or alcohol among Mexican migrants after migration to the U.S. [12].…”
Section: Introductionmentioning
confidence: 99%
“…People may receive benefit from migration (e.g., better employment, better health care), but they may also encounter migration stressors (e.g., loss of interpersonal ties, language barriers, discrimination) and suffer mental health problems (Berry & Kim, 1988; Du & Li, 2013; Du, Li, & Lin, 2014; Rogler, Cortes, & Malgady, 1991). Previous research has consistently found that migration was associated with more depressive symptoms (Chou, 2009; Silove, Sinnerbrink, Field, Manicavasagar, & Steel, 1997; Silveira & Allebeck, 2001; Vega, Kolody, & Valle, 1987).…”
Section: Introductionmentioning
confidence: 99%